ETCHING MECHANISM OF CCl4-DOPED GaAs GROWN BY MOCVD - Т. А. Bagaev; М. А. Ladugin; А. А. Padalitsa; А. А. Marmalyuk (Тонкие химические технологии)
Recently carbon-doped epitaxial layers become more attractive in most practical applications. In this paper we have considered the mechanisms of etching of CCl4-doped GaAs grown by MOCVD in the temperature range of 600–800°C. It has been shown that, as temperature increases, the etching of solid GaAs with the formation of volatile GaCl3 becomes the leading contribution to the growth rate reduction.